2011
DOI: 10.4278/ajhp.080926-lit-220
|View full text |Cite
|
Sign up to set email alerts
|

Promising Practices for the Prevention and Control of Obesity in the Worksite

Abstract: Purpose. To identify worksite practices that show promise for promoting employee weight loss. Data Source. The following electronic databases were searched from January 1, 1966, through December 31, 2005: CARL Uncover (via Ingenta), CDP, CINAHL, Cochrane Central Register of Controlled Trials, Cochrane Library, CRISP, Dissertation Abstracts, EMBASE, ERIC, Health Canada, INFORM (part of ABI/INFORM Proquest), LocatorPlus, New York Academy of Medicine, Ovid MEDLINE, SPORTDiscus, PapersFirst, PsycINFO, PubMed, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 138 publications
(278 reference statements)
0
13
0
Order By: Relevance
“…Our results reflect those from a recent national sample of smoking in health care providers. 22 The smoking prevalence of LPNs (28.9%) in VHA is higher than the rate of 20.6% reported by Sarna et al, 23 due to the inclusion of nursing assistants in the occupation group with LPNs, together representing 9% of the VHA workforce. Disparities and class issues may be greatest for nursing assistants, since they have the fewest years of formal education and the lowest incomes in the nursing profession.…”
Section: Disparities Drive Key Decisions Regarding Program Developmentmentioning
confidence: 52%
“…Our results reflect those from a recent national sample of smoking in health care providers. 22 The smoking prevalence of LPNs (28.9%) in VHA is higher than the rate of 20.6% reported by Sarna et al, 23 due to the inclusion of nursing assistants in the occupation group with LPNs, together representing 9% of the VHA workforce. Disparities and class issues may be greatest for nursing assistants, since they have the fewest years of formal education and the lowest incomes in the nursing profession.…”
Section: Disparities Drive Key Decisions Regarding Program Developmentmentioning
confidence: 52%
“…There is evidence of a modest reduction in weight as a result of worksite health promotion programs aimed at improving nutrition, physical activity, or both. Archer et al, 2011 (29) N=136 (various study designs)…”
Section: Description Of Reviewsmentioning
confidence: 99%
“…Some reviews recommended specific intervention types to the prevention of weight gain. Archer et al (29), for example, identified six promising practices with sufficient evidence for beneficial effects, including enhanced access to opportunities for physical activity in combination with health education, exercise prescriptions, multicomponent educational practices, weight loss competitions and incentives, and behavioral practices both with and without incentives.…”
Section: Effect Of Interventions On Weight-related Outcomesmentioning
confidence: 99%
“…This is exemplified by the Ma et al study where 7% of the initial target weight loss goal was achieved by 37% of the one-on-one coach-led intervention participants compared to only 14.4% of the self-led participants [4]. In addition, many studies from USA, Netherlands, Republic of Korea, UK, Germany, and Australia evaluate the continual promising effects of one-on-one intervention on health behavior and the effective elements of brief intervention overall [2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%